Analysis of leprosy in people under 15 years old in the city of Imperatriz-MA from 2015 to 2020: epidemiological pattern, clinical profile and quality of life of affected individuals (Research, Society and Development, 2022)
Leprosy is endemic and since ancient civilizations has been the target of elimination strategies. The data from the Brazilian Ministry of Health reveal the need to focus and expedite the diagnosis of leprosy in children under 15 years of age, who may be the contactors of untreated or unreported cases. It was intended to analyze the clinical-epidemiological profile of leprosy in children under 15 years of age in the period from 2015 to 2020, in the municipality of Imperatriz-MA. The study used a descriptive, qualitative approach, with field research. The subjects of the study were cases of Leprosy in children under 15 years old, of both sexes, notified in the period from 2015 to 2020 and residents in the municipality of Imperatriz-MA. Between 2015 and 2020, 107 cases of leprosy in children under 15 years old were notified, showing higher prevalence for Multibacillary and clinical form of undetermined notification. As for the evaluation of disability, the grade zero were the most notified. In this context, the results showed the importance of early diagnosis and effective treatment, aiming at improving the quality of life and not interfering with essential activities. Strategies were recommended by the health agencies to combat this picture of leprosy. It was concluded that it is of immeasurable importance to fight early the curve of leprosy cases in people under 15 years old in the country, especially in Maranhão. This measure, along with the search for early diagnosis should be a priority, as well as the completion of effective treatment for non-transmission.